Complexity of the Middle East Region and Power Rivalry Among Actors - Chaminda Kosala Wijekoon (Jurnal Kewarganegaraan, 2022)
Sovereignty is the supreme authority in the world and each state in the world is on its own to provide safety and security to its nation. In this context, states in the Middle East region engage in a struggle to achieve their competitive advantage to achieve regional hegemony and make sure the safety and security of the nation. This paper aims to discuss regional power projections to have a competitive advantage over resources. This study uses a qualitative research methodology with a focus on the study of Middle East geopolitics based on seven actors, among them four are state actors (Saudi Arabia, Iran, Turkey, and Yemen)and the other is non-state actors (Kurds, Al Qaeda, and ISIS). The Middle East is now at the center of world politics and has defined the rivalry between Iran and Saudi Arabia for nearly a century. The Arab world is witnessing a series of protests leading to the overthrow of powerful regimes in places like Libya, Tunisia, and Egypt. The conflict between Saudi Arabia and Iran is a central component of the Middle East security scene, expanding into both the Gulf and Arab-Israeli theaters. Their reaction to regional events has become a major reason for the crisis in the Middle East.